PERLINDUNGAN HUKUM BAGI MASYARAKAT YANG TELAH MENGIKUTI VAKSINASI - Hitaminah, Hj. Khusnul (JUSTNESS - Jurnal Hukun dan Agama, 2023)
Abstrack The background of this research is that there is a COVID-19 vaccination program that creates pros and cons in the community so that there is a need for protection for the community after vaccination. The problems studied in this study and the objectives can be formulated firstly to find out the legal protection for people who have participated in the vaccination against side effects after the implementation of the COVID-19 vaccination and secondly what legal remedies can be taken by the people affected by the implementation of the COVID-19 vaccination. The method used in this research is normative juridical, namely by reviewing the laws and regulations, legal theories related to the issues discussed. The results of this study show that there are two form of legal protection for the community after the implementation of COVID-19 vaccination in Indonesia, namely preventive and repressive legal protection and legal remedies that can be taken by the community if the accountability is not carried out, namely by ordinary civil lawsuits, Citizen lawsuits. , and class actions. Keywords: Vaccination, Legal Protection